De Facto Regimes in International Law - Essen, Jonte van (Utrecht Journal of International and European Law, 2012)
The ambiguous position of de facto regimes in international law has long been the subject of scholarly debate and a source of political conflict. An assessment of the current standing of these regimes in international law and the consequences of actions by international actors on this status has, however, been long overdue. The manner in which de facto regimes are regarded internationally has serious consequences for the individuals under the influence of this legal grey area. Therefore, the study into this problem and possible solutions is of great significance. The 2011 developments in Northern Africa underline the need of contemporary research into this area. This essay aims to clarify the position of de facto regimes in international law and the influence on their status by actions of international actors. The author first argues that de facto regimes have rights and obligations under international law, which provide them with (some form of) international legal personality. He then pleads for a reconsideration of the contemporary legal treatment of these regimes. The author argues against the current system of government recognition and proposes a system that better addresses the needs of both de facto regimes and the international community.